Implementasi Program Tahfidz Al-Qur'an dalam Pembentukan Karakter Religius Santri Madrasah Tsanawiyah - Abd Hamid; Muhammad Habiburrahman (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine the implementation of the Tahfidz Al-Qur'an program in forming the religious character of santri at MTS Yusuf Abdussatar and MTS Al-Ishlahuddin, West Lombok. The research employed a descriptive qualitative approach with field research design. Subjects included madrasah heads, tahfidz teachers, and santri participating in the tahfidz program. Data collection techniques included interviews, observations, and documentation. Data analysis used the Miles and Huberman model. The results indicate that: (1) the tahfidz program implementation is conducted well through three stages including planning, implementation, and evaluation with Monday-Thursday schedule, providing textbooks, and formative-sumative assessments; (2) the formation of santri's religious character is good according to indicators by applying methods of role modeling, habituation, counseling, reward and punishment through knowledge, awareness, practice, habituation, and value maintenance stages. Religious character indicators include akhlakul karimah, polite behavior, congregationCal prayer, dhuha prayer, Monday-Thursday fasting, prayer, greeting, routine imtaq, and attending Yasin-Ratib. The characters formed are religious, tawadhu', responsibility, istiqomah, tolerance, and achievement. The tahfidz program provides significant contribution to forming santri's religious character